IMPLEMENTASI METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN FIQIH DI MADRASAH ALIYAH HASYIM ASY’ARI JOGOROTO JOMBANG - Zanjabil, Fattaky; Umam, Khoirul (PAI FAI UNHASY Tebuireng Jombang, 2024)
This article discusses the implementation of the problem-based learning method in Islamic jurisprudence learning using qualitative research methods with a case study type that explores problems in detail and data collection is carried out in depth. Data collection was carried out through a process of observation, interviews and documentation by researchers, then reduced and checked using triangulation techniques to test the credibility of the data between one data and another. research conducted by researchers shows the results that: 1) The implementation of the problem based learning method is implemented through several stages, namely planning, implementation, and evaluation by involving students in accordance with the problems faced in the real world related to learning material in fiqh subjects in Madrasah Aliyah Hasyim Asy'ari Jogoroto Jombang. 2) Supporting factors for implementing problem based learning in this madrasah are support from school management, availability of adequate resources, teacher's ability to design and implement problem learning, as well as providing motivation by teachers so that students feel happy and comfortable with this method. The inhibiting factors are teachers having difficulty finding material to be taught, lack of understanding or support from student staff, limited time, and challenges for teachers to adapt the problem based learning method approach to the existing curriculum.